Kontribusi Seni Budaya Karungut Dalam Menyampaikan Cerita Alkitab Pada Anak Sekolah Minggu - Herikiswanto; Aristo; Lukas; Syahur, Heri (Institut Agama Kristen Negeri Palangka Raya, 2023)
The problem that will be discussed is how the art of karugut culture can be used as a medium for teaching Sunday school children and conveying the values ​​of the message of Bible stories by making karugut art as one of the media that can be used. The aim of this research is to develop the karkut art media as a learning medium for how Sunday school teachers can use thekarkut art media when teaching Sunday school children. The methods used in this research include: interviews, observation, literature study. From the results of the research, it is proven that by teaching using the sackut art method there is a significant increase as previously the attendance of Sunday school children was small but when using the sackut art the attendance and enthusiasm of Sunday school children increased.